(untitled) (Al-Academy, 2020)
This research deals with the audio part of the cinematic film, which is the sound and its elements inside the space of the cinema picture. It also deals with the psychological side of the sound and the effects made by the sound on the audience through the carefully studied use of the film maker in employing the sound and the picture. For the importance of this element, most of the directors were aware of the seriousness that sound causes to the cinematography, and consequently working as a whole such as the indications, meanings, symbols, metaphors ,transitions…etc. The research included the methodological framework which consists of the research problem, in which the researcher made the following question "how to employ the psychological dimension of sound in the motion picture" then the research importance, objectives, limits, and the researcher concluded by defining the terms. The theoretical framework included two sections the first of which is entitled (the psychological dimension of sound), which deals with the psychological dimension of sound and the effects made by the sound on the audience. It was supported by a number of sources. The second section was entitled (sound and its elements in the cinematic work). This section addressed the sound element and its employment inside the cinematic work through its elements. Then the research concluded with a number of indicators. The research procedures consist of the (research methodology, community, sample, tools and validity in addition to the units of analysis) then the analysis of the sample consists of analyzing the American film (Avengers Infinity War) produced in (2018) by the Russo brothers.